Management of indicators of loss and dilution in a mining activity - Lipo, Skender Bashkim; Polo, Nevina (International Journal of Scientific Research and Management (IJSRM), 2018)
Mining assets are unrepeatable and an important source for the development of a country. Their industrial exploitation is based on mining, metallurgical, economic, environmental, and state social factors. Mining factors such as production capacities, mining costs and the realization of indicators of loss and dilution are the determinants of the success of a mining activity. The value of a mining project, which is based on limited reserves, is very sensitive to loss indicators and dilution, as each lost tonnage of minerals affects the value of the resources. In this article, we will discuss the degree of impact of the above factors, while paying attention to achieving the most optimal indicators of loss and dilution. In mining activities with limited reserves and where the value of a mineral tone extracted from the ground is high, is required to increase the extract / loss ratio and maintaining a fair ratio between the indicators of loss and dilution